Sustainable strategies for Ebola virus disease outbreak preparedness in Africa: a case study on lessons learnt in countries neighbouring the Democratic Republic of the Congo - Caroline S. Ryan; Marie-Roseline D. Belizaire; Miriam Nanyunja; Olushayo Oluseun Olu; Yahaya Ali Ahmed; Anderson Latt; Matthew Tut Kol; Bertrand Bamuleke; Jayne Tusiime; Nadia Nsabimbona; Ishata Conteh; Shamiso Nyashanu; et al. (BMC, 2022)
Abstract Background From May 2018 to September 2022, the Democratic Republic of Congo (DRC) experienced seven Ebola virus disease (EVD) outbreaks within its borders. During the 10th EVD outbreak (2018-2020), the largest experienced in the DRC and the second largest and most prolonged EVD outbreak recorded globally, a WHO risk assessment identified nine countries bordering the DRC as moderate to high risk from cross border importation. These countries implemented varying levels of Ebola virus disease preparedness interventions. This case study highlights the gains and shortfalls with the Ebola virus disease preparedness interventions within the various contexts of these countries against the background of a renewed and growing commitment for global epidemic preparedness highlighted during recent World Health Assembly events. Main text Several positive impacts from preparedness support to countries bordering the affected provinces in the DRC were identified, including development of sustained capacities which were leveraged upon to respond to the subsequent coronavirus disease 2019 (COVID-19) pandemic. Shortfalls such as lost opportunities for operationalizing cross-border regional preparedness collaboration and better integration of multidisciplinary perspectives, vertical approaches to response pillars such as surveillance, over dependence on external support and duplication of efforts especially in areas of capacity building were also identified. A recurrent theme that emerged from this case study is the propensity towards implementing short-term interventions during active Ebola virus disease outbreaks for preparedness rather than sustainable investment into strengthening systems for improved health security in alignment with IHR obligations, the Sustainable Development Goals and advocating global policy for addressing the larger structural determinants underscoring these outbreaks. Conclusions Despite several international frameworks established at the global level for emergency preparedness, a shortfall exists between global policy and practice in countries at high risk of cross border transmission from persistent Ebola virus disease outbreaks in the Democratic Republic of Congo. With renewed global health commitment for country emergency preparedness resulting from the COVID-19 pandemic and cumulating in a resolution for a pandemic preparedness treaty, the time to review and address these gaps and provide recommendations for more sustainable and integrative approaches to emergency preparedness towards achieving global health security is now.